Long-term effects of cardiac rehabilitation in elderly individuals with stable coronary artery disease. Issue 9 (23rd April 2016) - Mandic, Sandra; Stevens, Emily; Hodge, Claire; Brown, Casey; Walker, Robert; Body, Dianne; Barclay, Leanne; Nye, Edwin R.; Williams, Michael J. A.
Abstract: Purpose : To compare exercise capacity and cardiovascular response to exercise in elderly individuals with coronary artery disease (CAD) who attend ongoing community-based maintenance cardiac rehabilitation (CR) versus age- and gender-matched healthy "very active" (HVA; ≥ 2000 kcal/week) and healthy "less active" (HLA; <2000 kcal/week) individuals. Method : Sixty-three participants (age: 72.3 ± 5.1 years; 62% men; n = 21 per group) completed the following assessments: (1) symptom-limited graded exercise test with expired gas analysis and bioimpedance assessment of cardiovascular function during exercise; (2) walking tests; (3) physical function; (4) anthropometry and (5) 12-month physical activity recall. Results : The CR group achieved 98% (range: 73–154%) of age- and gender-predicted peak oxygen consumption for healthy individuals. Peak oxygen consumption was lower in CR compared to HVA but not HLA group (VO2peak : CR: 19.0 ± 4.5, HVA: 23.7 ± 2.9, HLA: 20.7 ± 4.7 ml ·kg −1 ċmin −1, p = 0.001 versus HVA; p = 0.390 versus HLA). Peak heart rate was lower in CR compared to both HVA and HLA. Walking test results and cardiovascular and physical function were not different between the groups. Conclusions : Elderly individuals with CAD participating in maintenance CR have similar exercise capacity and cardiorespiratory response to exercise compared to their age- and gender-matched less active healthy peers. The findings support referral of elderly patients to community-based CR. Implications for Rehabilitation: Fitness benefits of long-term maintenance cardiac rehabilitation (CR) programs remain unknown. Elderly individuals with coronary artery disease participating in maintenance CR have exercise capacity and cardiorespiratory response to exercise similar to their less active healthy peers. Maintenance CR may play an important role prolonging independent living in elderly individuals.